Microfiber loop resonator for formaldehyde liquid sensing - Jali, Mohd Hafiz; Rahim, Hazli Rafis Abdul; Hamid, Sana Sulaiman; Johari, Md Ashadi Md; Yusof, Haziezol Helmi Mohd; Thokchom, Siddharth; Harun, Sulaiman Wadi; Khasanah, Miratul; Yasin, Moh (Elsevier, 2019)
This work employed the whispering gallery mode (WGM) of microfiber loop resonator (MLR) for formaldehyde (CH2O) liquid sensing application. A significant sensing response to different concentrations of formaldehyde liquid from 0% to 5% was observed due to the surface absorption and changeable refractive index resulting in different light attenuation in the silica microfiber. As the concentration increases, the output power of the MLR decreased linearly from −18.9 dB m to −36.2.dBm with sensitivity increased by a factor of 2.5 as compared to straight microfiber (SmF). As for resolution, the MLR improved by a factor of 3.28 as compared to SmF. © 2019 Elsevier GmbH